Multidimensional Separating Equilibria and Moral Hazard: An Empirical Study of National Football League Contract Negotiations - Conlin, Michael; Emerson, Patrick M. (The Review of Economics and Statistics, 2003)
This paper empirically tests for a multidimensional separating equilibrium in contract negotiations and tests for evidence of the moral hazard inherent in many contracts. Using contract and performance data on players drafted into the National Football League from 1986 through 1991, we find evidence that players use delay to agreement and incentive clauses to reveal their private information during contract negotiations. In addition, our empirical tests of the moral hazard issue indicate that a player's effort level is influenced by the structure of his contract.